2008
DOI: 10.1016/j.schres.2008.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosal area differences and gender dimorphism in neuroleptic-naïve, recent-onset schizophrenia and healthy control subjects

Abstract: The study of corpus callosal morphometry is important to unravel the underlying connectivity disturbance in schizophrenia. We studied the corpus callosal area in schizophrenia subjects compared to healthy subjects, while controlling for several confounders that could affect morphometric measures of the corpus callosum (CC). Areas of the whole CC and its sub-regions obtained by two geometric partitioning schemes were studied in 23 right-handed neuroleptic-naïve, recent-onset, schizophrenia patients and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…First, the number of segments entered into statistical analyses of size or anisotropy varied across the studies from 3 to 5 equal divisions, with a single 9-segment study (Rotarska-Jagiela et al, 2008) and two 6-segment studies (Keshavan et al, 2002; Goghari et al, 2005) employing unequal anatomical partitioning schemes (Witelson et al, 1989; Highley et al, 1999). Second, few of the analyses based their segmentation on the medial axis of callosal outline (Downhill et al, 2000; Walterfang et al, 2008b), whereas most others used radial (John et al, 2008) or vertical (Bachmann et al, 2003) partitioning. Utilization of the medial axis, however, provides a better estimate of the shape irregularities of the corpus callosum, especially when more sagittal sections are outlined in addition to the midline, which has thus far been seldom done (Bachmann et al, 2003; Rotarska-Jagiela et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the number of segments entered into statistical analyses of size or anisotropy varied across the studies from 3 to 5 equal divisions, with a single 9-segment study (Rotarska-Jagiela et al, 2008) and two 6-segment studies (Keshavan et al, 2002; Goghari et al, 2005) employing unequal anatomical partitioning schemes (Witelson et al, 1989; Highley et al, 1999). Second, few of the analyses based their segmentation on the medial axis of callosal outline (Downhill et al, 2000; Walterfang et al, 2008b), whereas most others used radial (John et al, 2008) or vertical (Bachmann et al, 2003) partitioning. Utilization of the medial axis, however, provides a better estimate of the shape irregularities of the corpus callosum, especially when more sagittal sections are outlined in addition to the midline, which has thus far been seldom done (Bachmann et al, 2003; Rotarska-Jagiela et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These segments, starting anteriorly, were anatomically approximated as the rostrum and genu (segment 1), anterior body (segment 2), midbody (segment 3), posterior body (segment 4) and splenium (segment 5). Previous 5-segment parcellations of the corpus callosum in schizophrenia have not shown consensus over the isthmus identification (Venkatasubramanian et al, 2003), variously ascribing it to segment 4 (Bachmann et al, 2003) or 5 (John et al, 2008). We therefore chose to refer to segment 4 as the posterior body and to segment 5 as the splenium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an improved interhemispheric connectivity might be disadvantageous for patients with schizophrenia. This aspect is supported by John, Shakeel, and Jain (2008) proposing a so-called "hyperconnectivity" of interhemispheric fibers connecting temporal association cortices as a cause of positive symptoms of schizophrenia.…”
Section: White Matter Connectivity Abnormalities In Schizophreniamentioning
confidence: 85%
“…[13] The inconsistent findings may be a consequence of possible confounding factors, including age, [14] handedness, [15] gender, [16] chronicity of illness [17,18] and differences in CC partitioning schemes employed by the different studies. [19,20] In addition, it was suggested that it may also be owing to the heterogeneity in symptom profiles. [12,18] Schizophrenia is characterised by large heterogeneity, [12,18] and subtypes of schizophrenia may differ in neuroimaging-based measures of brain morphology.…”
Section: Articlementioning
confidence: 99%